2005
DOI: 10.1529/biophysj.104.056788
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Fluidity Is a Key Modulator of Membrane Binding, Insertion, and Activity of 5-Lipoxygenase

Abstract: Mammalian 5-lipoxygenase (5-LO) catalyzes conversion of arachidonic acid to leukotrienes, potent mediators of inflammation and allergy. Upon cell stimulation, 5-LO selectively binds to nuclear membranes and becomes activated, yet the mechanism of recruitment of 5-LO to nuclear membranes and the mode of 5-LO-membrane interactions are poorly understood. Here we show that membrane fluidity is an important determinant of membrane binding strength of 5-LO, penetration into the membrane hydrophobic core, and activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 69 publications
6
80
0
3
Order By: Relevance
“…The only part of 5-LOX demonstrated to penetrate the bilayer is the putative membrane insertion loop that contains Trp-75 in the PLAT domain. This amino acid has been proposed to insert ϳ9 Å deep into the bilayer (53). Thus, 5-LOX is tethered to the membrane with calcium activation, but its substrate is bound deep within the hydrophobic bilayer to the helper protein FLAP.…”
Section: Compartmentalizationmentioning
confidence: 99%
“…The only part of 5-LOX demonstrated to penetrate the bilayer is the putative membrane insertion loop that contains Trp-75 in the PLAT domain. This amino acid has been proposed to insert ϳ9 Å deep into the bilayer (53). Thus, 5-LOX is tethered to the membrane with calcium activation, but its substrate is bound deep within the hydrophobic bilayer to the helper protein FLAP.…”
Section: Compartmentalizationmentioning
confidence: 99%
“…The nuclear envelope was described as a location site of LT biosynthetic metabolon , with only FLAP integrally associated in the membrane (Woods et al, 1993). Binding of Ca 2+ to 5-LO induces interaction of 5-LO with nuclear membrane with higher affinity to phosphatidylcholine (Puustinen et al, 1988;Kulkarni et al, 2002;Pande et al, 2005). It has been revealed that under physiological conditions phosphatidylcholine content in nuclear membrane is higher than in plasma membrane (Sleight and Pagano, 1984).…”
Section: -Lipoxygenase Pathway Of Leukotriene Synthesismentioning
confidence: 99%
“…Membrane insertion of LOX-1 was monitored by FRET experiments, where protein tryptophans served as donors and the Pyrene PE fluorescent probe, incorporated into 1 mM LUVs at a concentration of 10 nM (probe/lipid molar ratio of 1:10 5 ), as a fluorescence acceptor. 35 Fluorescence emission spectra were recorded in the wavelength range from 300 to 600 nm, using an excitation wavelength of 295 nm. The binding isotherms were built as already reported.…”
Section: ■ Concluding Remarksmentioning
confidence: 99%
“…In-depth investigations performed by means of Fourier transformed infrared spectroscopy (FTIR), in both transmission and reflection modes, have shown that membrane binding and enzymatic activity of human 5-LOX increase with the degree of cis-unsaturation of the lipid acyl chain. 35 Conversely, possible effects of LOXs on membrane properties remain largely unknown. In this context, it should be recalled that different animal and plant lipoxygenases (soybean LOX-1 included) have been shown to oxygenate substrates that are embedded within lipid bilayers.…”
mentioning
confidence: 99%